Census Hub as Centralizing Population Data: The European Union Experience - Pertiwi, Eka Bhella; Drajati Nugrahani, Henny Saptatia (UI Scholars Hub, 2020)
This study outlines the launching background of the Census Hub by the European Commission in 2011 as an initiative to centralize population and housing census data in the European Union. The aim of this paper is to analyze why the European Union wants to centralize its population and housing census data in an online system and also its benefits of looking at common issues that occur in the European Union. In order to elaborate on the reasons behind the launch of Census Hub, this article uses constructivism for European integration. The data sources used in this article are from the official publications published by the European Union, in particular the European Commission on Census Hubs. Other data will be obtained from online texts on integration, population, and housing in Europe. The results showed that the launching of the Census Hub is one of the the European Union endeavor to integrate Europe, not only by expanding its territory to the East. European integration can be done in all aspects of life, one of which is integrating population and housing census data. The ambition of European integration is an old desire for fulfilling European values and norms for welfare of citizens who live in its territory.